Stable Water Isotope Assessment of Tundra Wetland Hydrology as a Potential Source of Arctic Riverine Dissolved Organic Carbon in the Indigirka River Lowland, Northeastern Siberia - Takano, Shinya; Yamashita, Youhei; Tei, Shunsuke; Liang, Maochang; Shingubara, Ryo; Morozumi, Tomoki; Maximov, Trofim C.; Sugimoto, Atsuko (Frontiers in Earth Science, 2021)
Arctic tundra wetlands may be an important source of dissolved organic carbon (DOC) in Arctic rivers and the Arctic Ocean under global warming. We investigated stable water isotopes and DOC concentrations in wetlands, tributaries, and the mainstream at the lower reaches of the Indigirka River in northeastern Siberia during the summers of 2010−2014 to assess the complex hydrology and role of wetlands as sources of riverine DOC. The wetlands had higher values of δ18O and DOC concentrations than the tributaries and mainstream of the Indigirka River, suggesting that the wetlands can be a source of DOC for the river mainstream through the tributaries during summer. Couplings of temporal variations in δ18O and DOC in one tributary showed that mainstream water flowed into the tributary during relatively high river level periods in summer, whereas high-DOC water in the downstream wetlands could be discharged to both tributary and mainstream at lower river levels. Therefore, since the water level of the Indigirka River gradually decreases after the snowmelt season, the DOC contribution of the downstream wetland water to the river mainstream potentially increases from late summer to autumn with a decrease in the river level.